Food addiction among medical college students in Bengaluru city: a cross sectional study - Soman, Marvel K.; G. S., Vidya; M., Shashikala (International Journal Of Community Medicine And Public Health, 2024)
Background: Food addiction has specific connotations with respect to obesity which often results from the imbalance of food intake and energy expenditure. In countries like India, with relative abundance of food in recent years, and reduction in physical exercise, the rates of obesity have been on the rise. Obesity itself has been associated with the occurrence of metabolic syndrome which becomes a risk factor for diabetes mellitus and dyslipidaemia. This study aimed to assess the proportion of food addiction among medical college students in Bengaluru city. Methods: A descriptive study was conducted over a period of three months. The sampling technique employed was convenient sampling. The study population consisted of undergraduate medical students. The study involved a total of 174 participants. Inclusion criteria for participation included 1st year to 4th year MBBS students. The study tool utilized was the Yale Food Addiction Scale (YFAS). Results: Out of 174 respondents, the rate of occurrence of food addiction was 27.4%. Persistent desire or repeated unsuccessful attempts to quit was the most common symptom domain endorsed. Food addiction showed statistically significant association with BMI (Body Mass Index). Conclusions: This exploratory study suggests that food addiction may be present in a proportion of young aged medical students. The association of food addiction with higher weight and BMI suggests propensity to develop metabolic syndrome, and the need to evaluate interventions that could modify phenomenological expression of food addiction.